Imagineering, or what Images do to People: Violence and the Spectacular in the Seventeenth-Century Dutch Republic. Issue 1 (April 2021) - Korsten, Frans-Willem; van der Haven, Cornelis; Leemans, Inger; Vanhaesebrouck, Karel; van Duijnen, Michel; De Bruyn, Yannice
Abstract : This article studies the visual representation of violence in the Dutch Republic and the growth of a "staple market of images" in the early modern period. It introduces and employs the concept of imagineering for analysing what images can do to people when circulated in the context of a fast-expanding market. The advancement of the early modern print industry and imagery marketing produced a swirl of violent images. It was through this "spectacle of violence" and its related sensory and embodied experiences, that new ways of looking were introduced, which helped to craft new selves and realities. As the public manifestation of violence by ruling powers became less dominant, violence could become a matter of private consumption; a commodity to be enjoyed. Producers needed to create new markets as well as serve an existing one, satisfying clients in their inquisitive search for knowledge and excitement. Imagineering was not just a mimetic duplicate of its historical context, here, it performatively altered the imagination through the effective use of a new cultural infrastructure that enabled a visual abundance and continuous repetition and remediation of images.